Kesediaan guru dalam melaksanakan rancangan pendidikan individu dalam pendidikan islam bagi pelajar pendidikan khas - Moridan, Suhaimie (2013)
The Individualized Educational Plan (RPI) is one of the approaches towards the achievement of the individual teaching and learning objectives for special education students. It also concentrates on the different level of individual achievement and ability. The aim of this research is to survey the implementation readiness of Individualized Educational Plan (RPI) among Islamic Studies teachers in Muar and Batu Pahat districts. This research is conducted by using a combination of methods which involves 93 of Islamic Studies teachers. Questionnaires and interview are used as instruments in this research. The data were analyzed using SPSS for Windows (version 19.0), using descriptive statistics such as percentages, frequencies and mean. This research found that attitude of teachers are positive in implementing Individualized Educational Plan. While, the level of knowledge and level of skills are high. On the other hand, the most teaching strategies by teacher is “teacher-centred”, followed by “student-centred and third is “ material-centred”. There are no significant difference in attitudes, level of skills and teaching strategies based on teachers’ accreditation categories in implementing Individualized Educational Plan for special education students in Islamic education. However there is significant difference the level of teachers' knowledge. In addition, the research found that almost all respondents indicated that they require special training courses to strengthen the Individualized Educational Plan implementation in the Islamic education. The finding of this research can be used as references and recommendations related to the implementation of Individualized Educational Plan for special education students in Islamic Education.